ANALISIS IMPLEMENTASI GOOD CORPORATE GOVERNANCE DI BANK BPR JATIM BANK UMKM JAWA TIMUR CABANG BONDOWOSO - Lailatul Holifah (Accounting Journal of Ibrahimy (AJI), 2025)
Good corporate governance was a factor that can determine the success and sustainability of a corporate entity. In banking magazines, BPR Jatim Bank, a micro, small, and medium enterprise bank in East Java, implements good corporate governance to support its operational activities. This study used a qualitative approach, aimed to illustrate the implementation of good corporate governance at BPR Jatim Bank, a micro, small, and medium enterprises bank in East Java, Bondowoso branch. Data collection techniques were carried out through observation, interviews, and documentation in May 2024. Furthermore, data processing and analysis utilized reduction, display, and conclusion drawing. The conclusion of this research was that the implementation of good corporate governance plays a significant role in decision-making, which was part of corporate governance, and it had become a necessity for companies to apply it effectively, not only to control and ensure the sustainability of the company. Operational activities had been carried out quite well with the presence of good corporate governance, as evidenced by the smooth functioning of each division's SOPs, which apply the five principles of good corporate governance: transparency, accountability, responsibility, independence, and fairness. It was hoped that the results of this research can serve as information for various stakeholders so that they can apply and enhance the implementation of good corporate governance